2019
DOI: 10.3390/ijms20194709
|View full text |Cite
|
Sign up to set email alerts
|

Activating Hippo Pathway via Rassf1 by Ursolic Acid Suppresses the Tumorigenesis of Gastric Cancer

Abstract: The Hippo pathway is often dysregulated in many carcinomas, which results in various stages of tumor progression. Ursolic acid (UA), a natural compound that exists in many herbal plants, is known to obstruct cancer progression and exerts anti-carcinogenic effect on a number of human cancers. In this study, we aimed to examine the biological mechanisms of action of UA through the Hippo pathway in gastric cancer cells. MTT assay showed a decreased viability of gastric cancer cells after treatment with UA. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…The Hippo signaling pathway is a tumor inhibition pathway that was discovered in recent years, of which LATS1 and LATS2 kinase are two important components and have many important biological functions. LATS1 and LATS2 are involved in the occurrence and development of GC [15].…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway is a tumor inhibition pathway that was discovered in recent years, of which LATS1 and LATS2 kinase are two important components and have many important biological functions. LATS1 and LATS2 are involved in the occurrence and development of GC [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a controversial notion that YAP overexpression alone is related to the development of GC, several studies have identified YAP1 as an oncoprotein in the stomach. In normal and proliferating normal gastric epithelium, low or moderate levels of YAP1 expression are detected, whereas significantly elevated YAP1 levels are consistently observed in both primary and metastatic GC [23,24]. YAP1 expression is strongly positively correlated with lymphatic metastasis and shortened overall survival time, indicating that YAP may be used as an independent prognostic marker for GC [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, deficiency or inactivation of NF2, which functions to initiate and orchestrate the Hippo pathway ( 58 ), has been reported to be a frequent tumorigenic event in several cancer types ( 64 – 66 ). Furthermore, the upstream regulator of the Hippo pathway, ras association domain family (RASSF), suppresses cancer tumorigenesis ( 67 , 68 ) by regulating MST1/2 activity ( 59 , 60 ). However, how these regulators of the Hippo signaling are simultaneously disrupted in cancers, leading to constitutively inactivation of Hippo signaling, remains unclear.…”
Section: Discussionmentioning
confidence: 99%